Zimbabwe: Acquittal of imprisoned opposition leader shows growing cases of misuse of justice system to target critical voices - Amnesty International (Amnesty International, 2023)
Responding to yesterday’s High Court acquittal of opposition leader, Jacob Ngarivhume, who was sentenced in April to 48 months imprisonment for leading protests against government corruption, Khanyo Farisè, Amnesty International’s Deputy Director for Southern Africa, said: “His imprisonment is a travesty, and an affront to Zimbabwe’s constitution and the country’s international human rights obligations. No […]
Keywords: 2023-12 December

Security forces used rape and other sexual violence to crush “Woman Life Freedom" uprising with impunity - Amnesty International (Amnesty International, 2023)
A report demonstrates that security forces in Iran used rape and other forms of sexual violence, amounting to torture and other ill-treatment, to intimidate and punish peaceful protesters during the 2022 “Woman Life Freedom” uprising.
Keywords: 2023-12 December

Burundi: Amend gender-based violence law - Amnesty International (Amnesty International, 2023)
Burundi’s 2016 law against gender-based violence was a milestone achievement, bringing improved protection. However, it falls short of regional and international best practice, and in some instances undermines rather reinforces the fight against gender-based violence. This briefing proposes how to strengthen protections, including through revisions of the law.
Keywords: 2023-12 December